Katarzyna Buczek, Hugo Kołłątaj i edukacja, Wydawnictwo Uniwersytetu Warszawskiego, 2007, ss. 194 - Falkowska, Joanna (Biuletyn Historii Wychowania, 2008)
Katarzyna Buczek, Hugo Kołłątaj i edukacja, Wydawnictwo Uniwersytetu Warszawskiego, 2007, ss. 194